Bees and Fire: How does Fire in Longleaf Pine Savannas Affect Bee Communities? - Nicole Mitchell; Sarah Anderson Weaver; Raelene M. Crandall (EDIS)
Bees are efficient pollinators known to be key components of healthy forests. Thus, bees are often used as indicators of community response to restoration and disturbances, including fire. In longleaf pine savannas, the open canopies and floral resources that increase bee diversity and abundance are promoted by applying frequent, patchy prescribed fires. This publication is aimed to help fire and natural resource managers, landowners, and interested citizens learn more about the benefits of using fire to promote bee diversity in longleaf pine savannas.